2018 IEEE Latin American Conference on Computational Intelligence (LA-CCI) 2018
DOI: 10.1109/la-cci.2018.8625228
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Machine Learning Techniques for Anomaly Detection in the Internet of Things

Abstract: A major challenge faced in the Internet of Things (IoT) is discovering issues that can occur in it, such as anomalies in the network or within the IoT devices. The nature of IoT hinders the identification of issues because of the huge number of devices and amounts of data generated. The aim of this paper is to investigate machine learning for effectively identifying anomalies in an IoT environment. We evaluated several state-of-the-art techniques which can identify, in real-time, when anomalies have occurred, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The study in [ 47 ] uses machine learning approaches to investigate the identification of anomalies in the IoT context. It makes use of two datasets for time-series data and databases such as the NSL-KDD dataset for non-time-series data.…”
Section: Machine Learning—iot Network Anomaly Detectionmentioning
confidence: 99%
“…The study in [ 47 ] uses machine learning approaches to investigate the identification of anomalies in the IoT context. It makes use of two datasets for time-series data and databases such as the NSL-KDD dataset for non-time-series data.…”
Section: Machine Learning—iot Network Anomaly Detectionmentioning
confidence: 99%
“…In the comparative study executed by Brady et al (2018), kNN, Logistic Regression (LR), Linear Discriminant Analysis (LDA), Decision Tree (CART), and Naïve Bayes (NB) were the machine feature reduction, the maximum accuracy achieved in real-time detection was 80 percent. This was impressive in its regard; however, recent research have surpassed this accuracy.…”
Section: Machine Learning Applications With Many Features Make Traini...mentioning
confidence: 99%
“…Their results showed that a neighbor comparison and historical comparison are useful to predict anomalies within their proposed algorithm. Moreover, in [13] the authors evaluated some techniques suitable to identify realtime anomalies within an IoT network with the aim of offering practitioners a reference about when such techniques might be more appropriate.…”
Section: Related Workmentioning
confidence: 99%